Genetic diversity in Indian rice germplasm set using phenotypic and genotypic variables simultaneously - Singh, Nivedita; Majumder, Shana; Singh, Sanjay; Vikram, Prashant (The Indian Journal of Genetics and Plant Breeding, 2016)
Approximately 11% of the Indian rice varieties notified from 1969 to 2012 have IR-8 in their parentage. More than 30% notified varieties during this period are derived from germplasm with ‘IR’ in their parentage. India is one of the centers of diversity in rice and broadening of genetic base of cultivated rice can be successfully performed using indigenous germplasms. Genetic diversity among 42 Indian rice varieties (Oryza sativa L.), including landraces, aus cultivars and modern varieties of India were investigated for phenotype as well as genotype diversity. Genetic diversity analysis using genome-wide SNP panel suggested that aus cultivars, landraces and indica rice germplasm are genetically very close. The SNP panel was based on single copy genes thereby reflecting functional diversity of the germplasm set. The dendrogram based on molecular marker analysis grouped the 42 rice cultivars into 4 diverse groups. Further, population structure analysis also resulted to 4 sub populations. These sub population differentiated aus germplasm set from other accessions. Further, principal component analysis based on phenotype also suggested the closeness of aus cultivars, landraces and indica rice germplasm sets. Information generated through genetic, phenotypic and comprehensive diversity profiles in the present study can be efficiently utilized in breeding high yielding rice varieties.